Comparison of two behavioral tests for tinnitus assessment in mice - Fabrizio-Stover, Emily M.; Nichols, Grace; Corcoran, Jamie; Jain, Avni; Burghard, Alice L.; Lee, Christopher M.; Oliver, Douglas L. (Frontiers in Behavioral Neuroscience, 2022)
Animal research focused on chronic tinnitus associated with noise-induced hearing loss can be expensive and time-consuming as a result of the behavioral training required. Although there exist a number of behavioral tests for tinnitus; there have been few formal direct comparisons of these tests. Here, we evaluated animals in two different tinnitus assessment methods. CBA/CaJ mice were trained in an operant conditioning, active avoidance (AA) test, and a reflexive, gap-induced pre-pulse inhibition of acoustic startle (GPIAS) test, or both. Tinnitus was induced in awake mice by unilateral continuous sound exposure using a 2-kHz- or ½ octave- wide noise centered at 16 kHz and presented at 113- or 116-dB SPL. Tinnitus was assessed 8 weeks after sound overexposure. Most mice had evidence of tinnitus behavior in at least one of the two behaviors. Of the mice evaluated in AA, over half (55%) had tinnitus positive behavior. In GPIAS, fewer animals (13%) were positive than were identified using the AA test. Few mice were positive in both tests (10%), and only one was positive for tinnitus behavior at the same spectral frequency in both tests. When the association between tinnitus behavior and spontaneous activity recorded in the inferior colliculus was compared, animals with tinnitus behavior in AA exhibited increased spontaneous activity, while those positive in GPIAS did not. Thus, it appears that operant conditioning tests, like AA, may be more reliable and accurate tests for tinnitus than reflexive tests.